2020
DOI: 10.1111/tbed.13543
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Genetic Analysis of Recent and Emergent Virulent Newcastle Disease Viruses in Egypt

Abstract: Extensive vaccination against Newcastle disease virus (NDV) induced more selective immune pressure from hosts that enhanced the evolutionary process of NDV. Herein, we characterized 13 recently isolated NDV isolates from vaccinated chicken flocks during 2014–2017. Sequence analysis of F gene showed the presence of 112RRQKRF117 velogenic cleavage motif in 11 isolates, whereas the other two isolates (Ck/ME3/Eg/16 and Ck/ME5/Eg/16) showed the monobasic motif 112GGRQGRL117. Interestingly, isolate Ck/ME5/Eg/16 show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
17
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 41 publications
(51 reference statements)
3
17
1
Order By: Relevance
“…All viruses from the year 2006 (NDV/chicken/Egypt/2-4/2006; FJ969393, FJ969394, FJ969395) belong to genotype 2.II but are of velogenic pathotype with ICPI values between 1,6 to 1.8 and a have corresponding proteolytic polybasic cleavage site (RRQKR*FIG). The re-isolation of vaccine type virus in line with earlier description (Abolnik et al, 2004;Nagy et al, 2020) and it is conceivable, that emergency vaccination in flocks with suspected ND might lead to such double infections. Those circumstances have been considered by the OIE (OIE, 2018) when defining criteria for virulence: The definition includes the sequence information of the proteolytic cleavage site, but has the amendment "Failure to demonstrate the characteristic pattern of amino acid residues as described above would require characterization of the isolated virus by an ICPI test".…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…All viruses from the year 2006 (NDV/chicken/Egypt/2-4/2006; FJ969393, FJ969394, FJ969395) belong to genotype 2.II but are of velogenic pathotype with ICPI values between 1,6 to 1.8 and a have corresponding proteolytic polybasic cleavage site (RRQKR*FIG). The re-isolation of vaccine type virus in line with earlier description (Abolnik et al, 2004;Nagy et al, 2020) and it is conceivable, that emergency vaccination in flocks with suspected ND might lead to such double infections. Those circumstances have been considered by the OIE (OIE, 2018) when defining criteria for virulence: The definition includes the sequence information of the proteolytic cleavage site, but has the amendment "Failure to demonstrate the characteristic pattern of amino acid residues as described above would require characterization of the isolated virus by an ICPI test".…”
Section: Discussionsupporting
confidence: 53%
“…Sanger-sequence of isolate R1973/11 pointed to avirulent pathotype, but the ICPI result clearly revealed a velogenic pathotype. Such apparently contradicting results have been published before (Nagy et al, 2020;Tan et al, 2008), but were not further resolved. After observing such contradicting results, we plaque-cloned both isolates and were able to separate two different NDV: beside genotype 2.XXI virus, a vaccine type virus (genotype 2.II) was obtained.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Developing nervous manifestations following recovery from respiratory and digestive illness has been always associated with velogenic NDV in non-vaccinated broilers or in cases of improperly vaccinated infected flocks [43,44]. The data that were obtained from this study highlight that birds who were vaccinated with a G-II inactivated vaccine (G-1) showed the highest level of nervous manifestations (8%), while the birds who were vaccinated with the either the genotype VII rNDV or Autogenous NDV (G2 and G3) did not show any nervous system manifestations, suggesting a high level of protection in the G-2 and G-3 birds.…”
Section: Discussionmentioning
confidence: 99%